An A−D−Aʹ−Dʹ strategy enables perylenediimide-based polymer dyes exhibiting enhanced electron transport characteristics. (10th October 2019) - Tang, Zhonghai; Wei, Xuyang; Zhang, Weifeng; Zhou, Yankai; Wei, Congyuan; Huang, Jianyao; Chen, Zhihui; Wang, Liping; Yu, Gui
Abstract: In this work, we develop two new A−D−Aʹ−Dʹ type polymer dyes, namelyPPDIDTBT andPPDIDTBT-2F, containing perylenediimide (PDI), thiophene, and benzothiadiazole units. Both polymer dyes have high thermal stability and broad absorption throughout the UV–vis region. More importantly, the introduction of the second electron-withdrawing units, benzothiadiazoles, endows both polymer dyes with low-lying LUMO energy levels of −3.85 eV forPPDIDTBT and −3.88 eV forPPDIDTBT-2F . The charge transport properties of the two polymer dyes were examined by fabricating organic field-effect transistors (OFETs) with top-gate/bottom-contact configuration. Both polymer dyes exhibit enhanced electron transport characteristics with the highest electron mobility of 0.070 cm 2  V −1  s −1, which is among the highest values for PDI-based polymer semiconductors reported to date. Our results highlight that the A−D−Aʹ−Dʹ strategy is a useful approach in tuning orbital energetic and charge transport properties of polymer dyes for developing high-performance OFETs. Graphical abstract: Image 1 Highlights: Two new PDI-based polymer dyes were designed and synthesized. A−D−Aʹ−Dʹ strategy is a useful approach in tuning orbital energetic and charge transport properties. The electron mobility of 0.070 cm 2  V −1  s −1 is among the highest values for PDI-based polymers reported to date.